Analisis Tingkat Kepuasan Konsumen terhadap Kualitas Pelayanan Kefarmasian di Apotek Makmur Sehat Sukoharjo - Safira Khoirunisa; Retnowati Adiningsih (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Services carried out in accordance with established standards in the pharmaceutical field can create satisfaction for consumers. Pharmacies must be able to implement quality service standards. Inappropriate services will affect the sustainability of the pharmacy. Consumers who are satisfied with the services provided will potentially become regular customers of the pharmacy. The aims of this study to determine satisfaction consumer with the quality of pharmaceutical services at the Makmur Sehat Pharmacy, Sukoharjo. The research used a descriptive design and was carried out at the Makmur Sehat Pharmacy, Sukoharjo. The number of samples used was 385 respondents. sample selection using purposive sampling technique. The data collection tool used a questionnaire which included 5 dimensions in the form of dimensions of direct evidence/tangible, responsiveness, empathy, confidence, reliability to measure patient satisfaction. The results of the research dimensions are direct evidence/tangible of 80.42%, responsiveness of 83.12%, empathy of 82.81%, confidence of 80.75%, and reliability obtained results of 80.16 %. In general, the level of consumer satisfaction with the quality of pharmaceutical services at the Makmur Sehat Pharmacy Sukoharjo is classified as very satisfied.